High temperature x-ray diffraction of Zr-2.5Nb during thermal cycling in vacuum; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Tumanov M. Mikhail (2017, 2017)
Title screen